PENGARUH LAMA PENYIMPANAN DAN WARNA KERABANG TERHADAP KUALITAS INTERNAL TELUR ITIK TEGAL - Dian Lestari; Riyanti .; Veronica Wanniatie (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The purpose of this study were to (1) investigate the effects of storage time and eggshell colour of tegal duck eggs on the internal egg quality, (2) determine eggshell colour with the different storage time on score of haugh unit, pH of albumen, pH of yolk, and yolk colour. A total 72 duck egg with Completely Randomized Nest Design was used in this study. The treatments consist of 3 storage time (0, 7, and 14 days) as the main plot factor, 2 treatments eggshell colour (bright and dark) as the nest plot factor and 4 replications. Orthogonal contrast test done if there is a real variable. Based on the result showed that duck eggshell colour (bright and dark) treatments on storage time 0, 7, and 14 days did not provide significant effect on score haugh unit, pH of albumen, pH of yolk, and yolk colour of tegal duck eggs. The treatment eggshell colour (bright and dark) with a shell thickness of 0.01 mm difference with storage time 0, 7, and 14 days give the same contribution on the internal duck egg quality.